Anti-inflammatory and immunosuppressive activities of flavonoids from medicinal plants - Amit Gupta; Sushama R Chaphalkar (Shahrekord University of Medical Sciences, 2016)
Introduction: Medicinal plants have been used to treat various immunological diseases. Nitric oxide (NO) including proliferation and CD14 monocyte surface marker has played an important regulatory role in various types of inflammatory processes. This study was aimed to evaluate or scrutinize the effect of flavonoid extracted from the leaves of Santalum album, Butea frondosa and Emblica officinalis for determining their anti-inflammatory and immunosuppressive activity on human peripheral blood mononuclear cells (PBMC) using hepatitis B vaccine antigen (20 μg/mL; 10 μl). Methods: Flavonoids extracted from these medicinal plants were prepared (0.5-10 mg/mL; 50 μl) and their effects on human PBMC proliferation were examined using HBsAg. The NO production including CD14 monocyte surface marker was also estimated. Results: All these flavonoids at higher doses demonstrated a significant decrease in proliferation, NO production and CD14 surface marker. This inhibitory effect was seen after 48 hours of treatment. Conclusion: These results may indicate the presence of anti-inflammatory and immunosuppressive activity in these medicinal plants.